Assessment of musculoskeletal disorders among cricketers playing in domestic clubs of Lahore - Abdullah Munir; Mehwish Akhtar; Amina Khalid; Haider Farooq Khan; Faiza Kiran; Gull Bahar (Journal of the Pakistan Medical Association, 2022)
Objective: To assess musculoskeletal disorders among male cricketers in an urban centre. Method: The cross-sectional study was conducted from October to November 2020 in Lahore, Pakistan, and comprised male cricket players aged 10-25 years playing in four domestic clubs. Data was collected about musculoskeletal disorders experienced during the preceding 12 months using the Extended Nordic Musculoskeletal Questionnaire. Data was analysed using SPSS 22. Results: Of the 89 players with a mean age of 19.24+3.12 years, 35(39.3%) were bowlers, 26(29.2%) were batsmen, 17(19.1%) were all-rounders, and 11(12.4%) were wicketkeepers. The anatomical distribution of disorder was lower-back 68(76.4%), shoulder 40(44.9%), neck 39(43.8%), upper-back 37(41.6%), knees 31(34.8%), ankle/feet 29(32.6%), thighs 27(30.3%), wrist/hands 18(20.2%), and elbows 17(19.1%). There were 22(24.7%) players who had at any time seen a doctor or a physiotherapist, while 24(27%) players had a history of taking sick leave. Conclusion: The most affected anatomical segments were lower-back, shoulder, knee, ankle and upper-back. Key Words: Musculoskeletal disorders, MSDs, Occupational health, Nordic musculoskeletal questionnaire extended version, NMQ-E.